Acute short-term multimodal treatment for newly arrived traumatized refugees: Reflections on the practical experience and evaluation - Wenk-Ansohn, Mechthild; Heeke, Carina; Böttche, Maria; Stammel, Nadine (Torture Journal, 2018)
Background:A short-term multimodal acute treatment program of approximately six months’ duration for newly arrived refugees at Center ÜBERLEBEN (Berlin Center for Torture Victims) was developed. The purpose of this study was to evaluate this program by examining changes in PTSD, anxiety and depression symptom severity after treatment, and to reflect on practical experiences in carrying out the program. Methods:At the beginning (T1) and following completion of the short term treatment program (T2) patients in a single-group design were assessed with the Posttraumatic Stress Disorder Checklist for PTSD and the Hopkins-Symptom Checklist for depression and anxiety (per-protocol analysis). Results:Of the 92 patients who completed T1, 44 completed T2 assessments. Medium to large effect sizes were found for reductions in overall PTSD (d = 0.88), depression (d = 0.83), and anxiety symptoms (d = 0.67). While at the beginning of treatment (T1) 97.7% (n = 43) fulfilled diagnostic criteria for both PTSD and depression, and 95.5% (n=42) for anxiety, at T2, 70.5% (n = 31) fulfilled the criteria for clinically relevant PTSD, 79.5% (n = 35) for depression and 70.5% (n = 31) for anxiety. Discussion:Despite the high symptom load at the beginning of treatment, uncertainties regarding residence status, and the unstable living conditions, patients seem to benefit from the multidisciplinary short term treatment. This study adds preliminary evidence to the efficacy of multimodal treatment and suggests that improvements in symptom severity can be achieved within the often extremely stressful period after arrival.